Digital Transformation Through Business Model Innovation : A Qualitative Study Comparing German Private Family and Publicly Listed Non-Family Firms - Menth, Percy; Hnilica, Jiří, 1976-; Špaček, Miroslav, 1954-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Assumed a variance between the established paths and opportunities occurring from the new, digital technologies, the aim of this dissertation thesis is to better understand why firms can struggle on digital transformation through business model innovation. In depth, I will study what specific characteristics of German private family firms and publicly listed non-family firms can influence potential struggling. Furthermore, the aim of this dissertation thesis is to identify ways, how both could benefit from one another. Therefore, I will analyze interviews with 30 owners and C-level managers from 30 German private family firms and 20 C-level managers of 15 German publicly listed non-family firms facing digital transformations. This study’s key finding is, that it is not the firms’ nature, that may primarily foster digital transformation and business model innovation, but rather people, who could make the difference between struggling and success.
Vedoucí práce: Jiří Hnilica
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations